Dynamic reaction forces of an overhead crane on lifting - Spruogis, Bronislovas; Jakštas, Arūnas; Turla, Vytautas; Iljin, Igor; Šešok, Nikolaj (Transport, 2011)
In the recent period, girder bridge cranes are replaced with double-beam overhead cranes with a rectangular cross-section of the beams. In addition, new materials are used for producing them thus applying other values of allowable loads and deformations. The paper focuses on two overhead cranes working for JSC Vilniaus kranai (Vilnius Cranes). The presented mathematical model provides an opportunity to assess the structural peculiarities of the above introduced cranes. The calculated results of dynamic loads appearing in the beginning and the end of the lifting process and having an impact on the lifting mechanism and metal structure are provided in the article.First Published Online: 05 Oct 2011